Coupling finite elements and reduced approximation bases - Ammar, Amine; Pruliere, Etienne; Férec, Julien; Chinesta, Francisco; Cueto, Elias (European Journal of Computational Mechanics, 2009)
Models encountered in computational physics and engineering, usually involve too many degrees of freedom, too many simulation time-steps, too many iterations (e.g. non-linear models, optimization or inverse identification…), or simply excessive simulation time (for example when simulation in real time is envisaged). In some of our former works different reduction techniques were developed, some of them based on the use of an adaptive proper orthogonal decomposition and the other ones based on the use of separated representations. In this paper we are analyzing the coupling between reduced basis and standard finite element descriptions.